Role Of The Teacher In Getting Used To The Dhuha Prayer In Children Aged 4-5 Years: PERAN GURU DALAM PEMBIASAAN SHALAT DHUHA PADA ANAK USIA 4-5 TAHUN - Nurjanah, Siti; Rizqiyani, Revina; Rahma, Aulia (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
The Process of praying Dhuha not all children who are wrong or the way in which they move or recite the Dhuha prayer, the reason is because there are children who are just cool playing alone or playing with their friends regardless of what the teacher tells them to do and cause the child not to know and only cool alone. Therefore, the role of the teacher is needed to get used to worship dhuha prayer in children. This study aims to find out the role of the teacher in the habitation of Dhuha prayer in children aged 4-5 years at RA Al Huda, Pajar Village Mataram, Central Lampung Regency. The type of reascreach with a qualitative descriptive nature. Research used data collection techniques using interviews, observation an documentation. Data sources wew taken from various informant including the head and teachers of children aged 4-5 years at RA Al Huda, Pajar Matram Village, Central Lampung Regency. Based on the result of the study, it was conclude that the role of the teacher in the habituation of Dhuha prayers in children ades 4-5 years at RA Al Huda Pajar Matram Village, Central Lampung Regency, in this section the following conclusions can be drawn : the teachers as a demonstrator, the teacher sets an example starting from the i tention of ablution, ablution movements an procedures for dhuha prayers. The teachers as class manager, the teacher provides an explantion of the reasins why the dhuha prayers must be carried out every day and the teachers is able to overcome the obstacles that exist during the implementation of the Dhuha prayers habituation. The teachersacts as a mediator and facilitators, the teacrhers prepares media that supports the habituation of the Dhuha prayers with pictures of prayrs movements, the practice of ablution, the teacers as evaluator, namely in his role the teachers carries out continous evaluators or contonous evaluation or assessments of student learning outcomes, teaching skills and also the result obtained to determine the extent to which the learining process is successful.